Total sugar intake is associated with higher prevalence of depressive symptoms in obese adults - Li, Ping; Yin, Fuzai; Zhao, Yanru; Liu, Yali; Zhang, Ru; Wang, Jia; Lu, Wenqi; Wang, Qingsheng; Zhang, Jing (Frontiers in Public Health, 2023)
Background: The existing literature has repeatedly assessed the association between sugar-sweetened beverages and depressive symptoms, but studies of the association of total dietary sugar with depressive symptoms and of this association in obese adults are scarce. Thus, the purpose of this cross-sectional study was to assess the association between total sugar consumption and depressive symptoms in the study population and then in the population stratified by body mass index. Methods: This study was conducted in a nationally representative sample of 16,009 adults from the 2011–2018 National Health and Nutrition Examination Survey in the US. Total sugar intake was assessed by 24 h dietary recalls, and depressive symptoms were assessed by the nine-item Patient Health Questionnaire. Logistic regression models were used to evaluate the association between total sugar consumption and depressive symptoms. Results: Total sugar intake was positively associated with higher prevalence of depressive symptoms, and the adjusted odds ratio (95% confidence interval) of depressive symptoms for the highest versus lowest quintile of total sugar intake was 1.56 (1.18, 2.05). In stratified analysis, we found a positive association between total sugar intake and depressive symptoms in adults with body mass index > 30 kg/m2 (P for trend = 0.013), whereas no association was found in normal weight or overweight adults. Conclusions: A higher intake of total sugar was associated with increased odds of clinically relevant depressive symptoms among obese adults. Further studies are necessary to confirm the role of total sugar in depressive symptoms among obese adults.